Gender inequality and homicide: a cross-national examination - Heirigs, Mark H. (International journal of comparative and applied criminal justice, 2018)
Studies examining gender inequality and crime have often explored the connection between female victimisation and crime. However, feminist theories do provide a rationale for gender inequality affecting all crime, not just female victimisation. Using the ameliorative and the backlash hypothesis the current analysis examined gender inequality and homicide in 94 countries. Using a gender inequality index, we found that as gender inequality increased the homicide rate increased. This finding supports the ameliorative hypothesis, which states that as societies become more equal crime will decrease.